2022
DOI: 10.1002/ana.26350
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 and Mitochondrial Proteins in Neural‐Derived Exosomes of COVID‐19

Abstract: Objective As SARS‐CoV‐2 is known to invade neural cell mitochondria, a plasma system for quantifying central nervous system proteins in living humans was used to investigate neuropathogenic mechanisms of long‐COVID‐19. Methods SARS‐CoV‐2 proteins and mitochondrial proteins (MPs) in enriched plasma neuron‐derived extracellular vesicles (NDEVs) and astrocyte‐derived EVs (ADEVs) were quantified in resolved acute COVID‐19 without post‐acute sequelae of SARS‐CoV‐2 (PASC), PASC without neuropsychiatric manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 42 publications
1
84
0
Order By: Relevance
“…The authors concluded that this implicates a peripheral rather than central cardiac limit underlying PASC. It could reflect mitochondrial injury, as SARS-CoV-2 appears to be capable of invading at least neural cell mitochondria ( 74 ). But it would also be anticipated in the presence of persistent or progressive microthrombi ( 73 ).…”
Section: Formulating Hypotheses For Pasc Pathogenesismentioning
confidence: 99%
“…The authors concluded that this implicates a peripheral rather than central cardiac limit underlying PASC. It could reflect mitochondrial injury, as SARS-CoV-2 appears to be capable of invading at least neural cell mitochondria ( 74 ). But it would also be anticipated in the presence of persistent or progressive microthrombi ( 73 ).…”
Section: Formulating Hypotheses For Pasc Pathogenesismentioning
confidence: 99%
“…Elevated inflammatory markers, especially hsCRP, IL-6, and TNF-α could be due to higher severity of acute illness, 37 persistent immune activation, 38 and/or ongoing antigen stimulation from viral persistence. [39][40][41][42][43] The correlation between these markers and peak VO2 could arise from a common cause of PASC, or these markers could be on the causal path from SARS-CoV-2 infection to symptoms and reduced exercise capacity in Long COVID (Figure 4). Multiple studies have demonstrated that IL-6 may be elevated in PASC.…”
Section: Connections Between Inflammation Reduced Exercise Capacity A...mentioning
confidence: 99%
“…Even in the absence of phase separation, the high IDRs in the N protein can significantly accelerate aggregation of amyloid fibrils in vitro, whereas the structurally stable S protein of SARS-CoV-2 had no effect on ⍺-synuclein aggregation in SH-SY5Y cells [ 232 ]. Perhaps not coincidentally, the mean levels of N proteins in neuron-derived extracellular vesicles (NDEVs) isolated from plasma of subjects with PASC and neuropsychiatric (NP) manifestations were significantly higher compared to PASC subjects without NP; resolved, acute COVID-19 subjects without PASC; and healthy controls [ 233 ]. Similarly, Neuro-PASC patients exhibit higher T cell responses to the nucleocapsid protein compared with control convalescent patients, supporting the theory that a persistent reservoir of the N protein is responsible for the activation of unique immunological signatures biased towards N proteins in Neuro-PASC individuals [ 234 ].…”
Section: Sars-cov-2 Proteins Phase Separation Disrupt Host Biomolecul...mentioning
confidence: 99%